Uji Lapang Pakan Bervaksin Aeromonas hydrophila pada Lele Dumbo di Daerah Banyumas - Dini Siswani Mulia; Irma Tri Susanti; Heri Maryanto; Cahyono Purbomartono (Universitas Sebelas Maret, 2015)
The main problem in the cultivation of African catfish is a disease MAS (Motile Aeromonas Septicemia) Aeromonas hydrophila bacteria attack. In addition, other problems that also resulted in the successful cultivation of this fish is the high price of fish feed and the cost of production for the procurement of the feed. Needs to be studied the use of feed raw materials that utilize industrial waste as well as the use of vaccines in controlling disease MAS. This study aims to apply feed made from 3 waste, namely chicken feathers, pulp, and trash fish, then add the vaccine (vaccine feed) and tested in the field. Field test conducted in the village of Bangsa, District of Kebasen, Banyumas. This study uses a completely randomized design (CRD) with 3 treatments and 5 replications. The treatment consisted of P1 = vaccine feed 10 days; P2 = vaccine feed 15 days, and P3 = no vaccine feed (controls). Feed was given as much as 5% of the weight of fish / day. Research using plastic tarp length x width x height = 80 x 60 x 60 cm. African catfish which used a length of 10-13 cm with a weight of 7.3 to 21.1 g. Fish reared for 8 weeks. Parameters measured were immune response such as antibody titer, weight gain and length, specific growth rate (SGR), as well as survival. Parameters measured were supporting water quality parameters include water temperature, pH, and dissolved oxygen. Data were analyzed using Analysis of Variance (ANOVA) and Duncan Multiple Range Test (DMRT test) with a test level of 5%. The results showed that the vaccine could increase the production of antibody titers (P <0.05) compared to controls. The use of artificial feed of chicken feathers, pulp, and trash fish are added the vaccine (vaccine feed) can be applied in the field.Keywords: Aeromonas hydrophila, Banyumas, field test, vaccine feed